2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1617011
|View full text |Cite
|
Sign up to set email alerts
|

Noise Analysis of MREIT at 3T and 11T Field Strength

Abstract: In Magnetic Resonance Electrical Impedance Tomography (MREIT), we measure the induced magnetic flux density inside an imaging object subject to an external injection current. The magnetic flux density is contaminated with noise and this ultimately limits the quality of reconstructed conductivity and current density images. By using two methods to analyze amounts of noise in 3T and 11T MREIT systems, we found that a carefully designed MREIT study will be able to reduce the noise level below 0.1 nT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…11 This fact was experimentally verified for the phantom experiment. The histograms of background for real and imaginary images in a slice are shown in Figs.…”
Section: Distribution Of Noisementioning
confidence: 59%
See 2 more Smart Citations
“…11 This fact was experimentally verified for the phantom experiment. The histograms of background for real and imaginary images in a slice are shown in Figs.…”
Section: Distribution Of Noisementioning
confidence: 59%
“…The standard deviation of this noise can be extracted from the background. 11,18 Therefore, if we assume that for each pixel inside the subject X R is the random variable representing the corrupted intensity in real images and X I is the random variable representing the corrupted intensity in imaginary images, we have for one pixel…”
Section: Distribution Of Noisementioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the B z signal is directly proportional to the amplitude of the injection current. Noise analyses showed that the noise level in B z data is inversely proportional to the product of the signal‐to‐noise ratio (SNR) of the MR magnitude image Ψ and the total current injection time Δ T (4, 13). We should increase the product ΨΔ T to be able to reduce the imaging current without deteriorating the quality of B z images.…”
Section: Introductionmentioning
confidence: 99%
“…As the first step toward these goals, Sadleir et al (2005a) examined noise levels in measured magnetic flux density using two MREIT systems at 3 and 11 T field strengths. They found that typical noise levels were about 0.25 and 0.05 nT at 3 and 11 T, respectively, at a voxel size of 3 × 3 × 3 mm 3 .…”
Section: Introductionmentioning
confidence: 99%